2010
DOI: 10.1258/ijsa.2010.009572
|View full text |Cite
|
Sign up to set email alerts
|

National audit of asymptomatic screening in UK genitourinary medicine clinics: case-notes audit

Abstract: A national audit of screening of asymptomatic patients seen in UK genitourinary medicine clinics in 2009 was conducted against the national guidelines. Data were aggregated by regions and clinics in regions, allowing practice to be compared within and between regions, as well as to national averages and against national guidelines. The case-notes of 4428 patients were audited. Performance was over 80% against the national guidelines for screening of asymptomatic heterosexual men, men who have sex with men (MSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…At the same time, some categories in which the median proportion tested was 100% also included studies that reported relatively low levels of testing. For example, 33.6% of study participants in a study of people who use drugs were tested for HBV (39), and 13.0% of study participants in a study of asymptomatic patients in genitourinary medicine clinics were tested for HCV (59). However, we believe that our review findings around testing uptake are of limited value in assessing testing uptake levels in these populations because few studies had the specific purpose of examining HBV and HCV testing uptake.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, some categories in which the median proportion tested was 100% also included studies that reported relatively low levels of testing. For example, 33.6% of study participants in a study of people who use drugs were tested for HBV (39), and 13.0% of study participants in a study of asymptomatic patients in genitourinary medicine clinics were tested for HCV (59). However, we believe that our review findings around testing uptake are of limited value in assessing testing uptake levels in these populations because few studies had the specific purpose of examining HBV and HCV testing uptake.…”
Section: Discussionmentioning
confidence: 99%
“…67 The difference in approach to screening for men as opposed to women has probably developed as a result of widely held perceptions that young men are infrequent attenders at general practice whereas women are believed to attend more frequently and have multiple opportunities for screening as part of 'routine' visits for related health needs such as contraception. Data do not support this view 16 and the vast majority of men have attended their GP within the last year. 59 In spite of this, there appears to be a mismatch between GP's perceptions of men's low attendance rates and reality.…”
Section: Introductionmentioning
confidence: 93%
“…[13][14][15][16][17]. In brief, this is a compartmental transmission model which describes heterogeneous sexual behaviour that was parameterised by behaviour data from a number of key UK surveys and national surveillance data and with the natural history of NCNGU being informed from data in the literature.…”
Section: Model Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, screening tests for HIV are now offered routinely in various settings, for example, antenatal assessments and genitourinary medicine clinics 6 7. Screening in these settings alone, however, is not enough to detect all early cases of HIV.…”
Section: Introductionmentioning
confidence: 99%